Perlindungan Hukum Bagi Pengguna Jasa Internet Terhadap Kerahasiaan Data Pribadi - Anakotta, Fredrik; Haliwela, Nancy Silvana; Pariela, Marselo Valentino Geovani (PATTIMURA Legal Journal, 2024)
Introduction: In the current era of globalization, the internet plays a very important role in human life. In addition to playing an important role, there are also adverse impacts that harm internet service users such as personal data leaks. The confidentiality of personal data was leaked in 2022, including indihome customer data, as many as 26 million customer data were traded on BreachForms by Bjorka. The data is in the form of keyword search history, user info such as email, name, to Population Identification Number. Purposes of the Research: A form of legal protection for the public regarding the security of personal data and consumer rights that are not fulfilled. Methods of the Research: The research method used is normative juridical, namely by examining various laws and regulations and other literature related to the research. Results Originality of the Research: The results of this study show that the form of legal protection for internet service users against the confidentiality of personal data consists of three forms, namely the form of supervision of personal data, the existence of the principle of personal data security protection, where internet service providers are obliged to maintain the security of internet service user data, the existence of personal data security from unauthorized parties, for which the Government, Internet Service Providers, Law enforcement officials are obliged to supervise and secure all forms of internet networks, for example by deleting or locking personal data if it has been used by the user, as well as strengthening legal arrangements related to the misuse of personal data confidentiality. Quickly handle various cases of abuse of the confidentiality of personal data of internet network users so that it has a deterrent effect.